Kacip Termodifikasi dengan Delapan Mata Penyayat Guna Mendukung Usaha Kacang Mente - B. Yokasing, Yohanes; Abdullah, Amiruddin; Pangalinan, Antonius (JURNAL FLYWHEEL, 2017)
“Kacip ceklok” is a cutting tool for cashew nut shells, which consist of 2 blades that used to help remove the cashew nuts from the skin. The results obtained from these cuts, still requires the removal. At this step,the process require a precision and circumspection so that the beans are not cracked, and not contaminated byCNSL oil.To realize it, kacip ceklok has been modified by adding more blades and become 8 blades. In addition, changes are also made on the size of the “kacip” eyes are varied into 3 groups of small size, medium and large. Specifications of the modifiedkacip are Length 600 mm, 280 mm height, adjustable 8 kacipblades and 3 cranks drive. The production ability of modified “kacip ceklok” is ± 74 seconds per peanut.The total percentage of cashew nuts from the results of the study for stripping of 9 seeds of mente in 3 size groups was 88.8 percent.Further studies are needed on the more grouping of mente seed dimensions and easier toadjust the kacip eyes. Keywords :Cashew seeds, kacip ceklok, cashew nuts.